The evolution of the international legal regulation of the protection of cultural property in the event of armed conflict - Yu. V. Puzyreva (Московский журнал международного права, 2023)
INTRODUCTION. In recent decades, there has been an escalation of armed clashes in the territories of African states, the states of the Middle East and Central Asia with the participation of military formations, international terrorist groups that everywhere use the practice of attacking and looting cultural property as a military strategy. In this regard, of scientific and practical interest is a comprehensive study of the legal and organizational foundations of international legal regulation of the protection of cultural property during armed conflicts, evaluation of their effectiveness and identification of promising tasks for the development of additional measures and strategies for the preservation of cultural heritage, taking into account new challenges and threats.MATERIALS AND METHODS. This paper examines the provisions of key international treaties, decisions of the main bodies and specialized agencies of the UN, which together form the existing international legal regime for the protection of cultural property in armed conflict. The author also analyzes the jurisprudence of international criminal justice bodies on bringing individuals to justice for deliberate attacks on cultural sites as part of hostilities. Special attention is paid to the study of scientific works of both domestic and foreign scientists, within which international legal concepts are formed, designed to resolve existing problems in the current international legal regulation of the issue under study, as well as to form promising concepts in the framework of the development of the doctrine of international law. The methodological basis is made up of general scientific and special research methods.RESEARCH RESULTS. According to the results of the study, it was found that during the XX century states have consistently developed norms for the protection of cultural property from threats associated with armed conflicts, while the XXI century was marked by best practice in the application of the rules on liability for attacks on cultural property in situations of armed conflict in the activities of international justice bodies. In addition, it was determined that for the first time in the history of UN peacekeeping, the UN Security Council tested the mandate of the Multidisciplinary Integrated Stabilization Mission in Mali, in which the peacekeeping contingent, among other things, performed the tasks of protecting, safeguarding and restoring cultural heritage sites together with UNESCO. It seems significant to identify and generalize the prospects for the development of new international legal measures for the preservation of cultural heritage for future generations, taking into account the changing nature of armed conflicts, the intensification of the activities of international terrorist groups and the growing practice of destroying the centuries-old cultural heritage of peoples in the framework of the so-called “cultural cleansing". The topical aspect of the study was the establishment of new approaches of states to the protection of cultural heritage as a means of ensuring international peace and security.DISCUSSION AND CONCLUSIONS. The publication presents the author's objective assessments of the established international legal framework, judicial practice of international criminal justice bodies, as well as doctrinal approaches of both domestic and foreign scientists on the issue of international legal regulation of the protection of cultural property during armed conflicts. Separately, the forms of international legal cooperation of states at the UN site within the framework of the UNESCO profile organization for the development of modern regulatory and organizational foundations for the interaction of the competent authorities of states to prevent and suppress the destruction of cultural heritage, as well as the looting and illegal export of cultural property in the event of an armed conflict, especially terrorist groups.